Production of Recombinant Echinococcus granulosus Antigen B Subunits, In Order to Using Of Them in Serodiagnostic Tests of Hydatidosis - R Pazoki; B Kazemi; MR Nazari; J Masoud; MR Akbari (Tehran University of Medical Sciences, 2007)
Background: Hydatidosis is one of the most important helminthiasis, and is a public health problem in many regions of the world. Methods: With the aim of production of recombinant subunits of antigen B, two different sequences of Echinococcus granulosus Antigen B, acquired from Gene Bank and amplified with specific primers via RT-PCR reaction. The amplified fragments (HI, HII) cloned into pTZ57R T.vector, and then subcloned into pGEMEX-1 expression vector. Resaults: The SDS-PAGE performed after induction of cloned genes, and production of about 35 K.Da recombinant fusion proteins were confirmed for either two cloned genes. The immunogenicity of the recombinant fusion proteins were tested using double diffusion and immunoblotting. Both recombinant fusion proteins derived from lysate of transformed bacteria, were reactive for antibodies in serum of cystic hydatid patient. Conclusion: The produced recombinant antigen B subunits can be use in seroldiagnostic tests of hydatidosis, after purification.